Computational intelligence techniques in engineering - Marques, Viriato M. (2008)
This article shows how CI techniques overpass the strict limits of Artificial Intelligence (AI) field and can help solving real problems from distinct engineering areas: Mechanical, Computer Science and Electrical Engineering. An introduction to each of the CI main areas is made and three systems are briefly described. The results are, in each case, very promising